Happy Tummy / Nur Atasha Rusley - Rusley, Nur Atasha (2021)
Happy Tummy is a trademark for our product which is TFN Brownies. The main objective is to achieve for the business is to offer variety of crispy and crunchy brownies to our customer with affordable price and luxurious taste of sweetness. Moreover, Happy Tummy have been using Facebook (FB) as a main medium for us to promote and market our product. This day, the usage of social media as a medium for marketing is very important since people in this decade always check out their mobile phone for any update. Moreover, from using social media our company can easily communication and interact with our customer. According to the customer review, our product gave a fantastic taste and flavour because the indulgence of the brownies makes our customer remembered the taste. Besides that, our customer also comment that our brownies have a premium taste that there are variety of brownies that make them to keep repeating our product. This product also has purchased by customers rapidly due to the cheapest and affordable price. Hence, this product provides a good insight for the continuation of sale to our existing and new customers. Since early of its opening, Happy Tummy have been sold TFN Brownies more than 100 packages for all different flavour. Increasing demands for our product results into a good profitable sale revenue to our business project. Therefore, Happy Tummy is a good product of choice that can be further expanded to many different areas as the business keeps on growing until this day. Hence, the usage of social media is very vital in promoting and marketing our company and product to the exist and new customers in order to get their trust for our product.